Control systems engineering - Nise, Norman S. (John Wiley & Sons, 2011)
Highly regarded for its accessible writing and practical case studies, Control Systems Engineering is the most widely adopted textbook for this core course in Mechanical and Electrical engineering programs. This new sixth edition has been revised and updated with 20% new problems and greater emphasis on computer-aided design